2009
DOI: 10.1364/oe.17.000649
|View full text |Cite
|
Sign up to set email alerts
|

Tree array quantum cascade laser

Abstract: A monolithic coupling scheme for mid-infrared quantum cascade laser arrays is investigated with respect to brightness enhancement. The tree-shaped resonator enables parallel coupling of six laser elements into a single element by means of several Y-junctions. Phase-locking is observed on the basis of far field analysis, and leads to in-phase emission on both sides of the device. The experimental results match calculated far field profiles and demonstrate a high level of modal control when driven far above thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Obtaining the coherence within an array relies on the ability to control the coupling between individual lasers. Inspired by concepts developed in more mature, shorter wavelength diode laser systems, several coupling schemes, including coupling through exponentially decaying fields outside the high index dielectric core (evanescent-wave coupled) [27][28][29], through feedback from external reflectors (diffraction-wave coupled) [30], connecting two ridges to one single-mode waveguide (Y coupled or tree coupled) [31][32][33][34][35], through lateral propagating waves (leaky-wave coupled) [36][37][38] and combining gradedphotonic-heterostructure (GPH) QCLs with a ring resonator [39], have exhibited excellent performance on phase-locking QCL arrays, especially in mid-infrared range.…”
Section: Brief Review Of Qcl Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining the coherence within an array relies on the ability to control the coupling between individual lasers. Inspired by concepts developed in more mature, shorter wavelength diode laser systems, several coupling schemes, including coupling through exponentially decaying fields outside the high index dielectric core (evanescent-wave coupled) [27][28][29], through feedback from external reflectors (diffraction-wave coupled) [30], connecting two ridges to one single-mode waveguide (Y coupled or tree coupled) [31][32][33][34][35], through lateral propagating waves (leaky-wave coupled) [36][37][38] and combining gradedphotonic-heterostructure (GPH) QCLs with a ring resonator [39], have exhibited excellent performance on phase-locking QCL arrays, especially in mid-infrared range.…”
Section: Brief Review Of Qcl Arraysmentioning
confidence: 99%
“…This understanding of the coupling mechanism is important to exploit Y-coupling in midinfrared QCL arrays with complex structures for high output performance. Then Hoffmann et al reported a tree-shaped resonator enabling parallel coupling of six laser elements into a single element by means of several Y-junctions (see Figure 7(a)) [33]. The parallel-coupled branches had three different lengths, which led to complex requirements for the propagating super-modes.…”
Section: Brief Review Of Qcl Arraysmentioning
confidence: 99%
“…16 Array fabrication via modulating the cap-layer thickness, rather than etch and regrowth, has also provided narrow-beam, in-phase-like operation to drive levels at least 10Â threshold. 17 For mid-IR QCLs, spatial coherence over large apertures has been reported from so-called PCDFB structures, 18,19 flared master-oscillator power-amplifier (MOPA) structures, 20 tree-type arrays involving Y branches, 21,22 and from evanescent-wave-coupled arrays. 23 PCDFB devices involve diffraction gratings, thus, have inherently low index contrast (Dn ¼ 0.006-0.008) 18 and have shown near-D.L., single-lobe operation, at k ¼ 4.6 lm, to only 10% above threshold and 0.5 W/facet peak pulsed power.…”
Section: W Near-diffraction-limited Power From Resonant Leaky-wave Comentioning
confidence: 99%
“…Y-branch coupled-ridge waveguides, which is one way to achieve global coupling, operating at λ ¼ 10.8 μm have demonstrated pulsed in-phase mode operation from six elements, but with no increase in brightness due to modal competition. 3 By employing resonant leaky-wave coupling for phase-locking arrays of antiguides, 4 global coupling has led to 5.5 W near-diffraction-limited (DL) power from five-element arrays operating at λ ¼ 8.4 μm. As described below, resonant leaky-wave coupling has also been employed for obtaining global coupling in THz phase-locked QCL arrays.…”
Section: Introductionmentioning
confidence: 99%